Demand estimation of full-cut promotion on E-commerce company - Wong, Jing Hui (2019)
Full-cut promotion is a type of promotion where customers spend a minimum threshold amount in a single order to enjoy a fixed discount amount for that order. This type of promotion is popular in China, particularly in E-commerce. However, there is no existing literature that estimates the promotion driven demand and optimizes the threshold and discount amount in the full-cut promotion.